Kategori dan Peran Tematis Argumen Klausa Verbal pada Bahasa Batak Toba - Febrika Dwi Lestari; Mulyadi Mulyadi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This paper describes the types of thematic role categories of verbal clause arguments in the Toba Batak language (BBT). This syntactic study is conducted through a qualitative approach with a listening technique in collecting oral and written data. Then the data is processed through commensurate and 'agih' methods, which are described through distributional and informal methods. The results show that the category of verbal clauses in BBT is divided into two parts: verbal and non-verbal. Verbal clauses consist of (1) transitive clauses, which are divided into medial active clauses, passive clauses, and reciprocal clauses; (2) intransitive clauses; and (3) semi-transitive clauses. Transitive clauses have the structure of P+O+S and S+P+O. Intransitive clauses are structured P+S and P+S+Ket. Furthermore, semi transitive clauses have S+P and S+P+Ket as their structures. The category of non-verbal clauses in BBT, namely clauses with non-verbal predicates, have nominal, numeral, adjectival, and adverbial (prepositional phrases) as categories in their predicates. The thematic role of BBT verbal clause arguments consists of two macro roles as actor and undergoer, while the special thematic role consists of agent, stimulus, experiencer, theme, locative and patient. This research is further expected to positively impact the development of BBT.